2020
DOI: 10.1186/s12896-020-0598-3
|View full text |Cite
|
Sign up to set email alerts
|

Intein-mediated recombinant expression of monomeric B22Asp desB30 insulin

Abstract: Background: Insulin controls hyperglycemia caused by diabetes, and virtually all treatments require exogenous insulin. However, the product's extensive post-translational modifications have hindered the manufacture of recombinant insulin. Result: Here we report a novel production method for a monomeric B22Asp desB30 insulin analog (B22D desB30 insulin). Its precursor, DPIP, is fused to an N-terminal chitin-binding domain and intein self-cleavage tag. The fusion protein is expressed and purified from E. coli an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…reported that the best temperature was considered 37 °C among investigated temperatures ranging from 15 to 37 °C for Ssp DnaB mini-intein fused to human GLP-1/7-36 ( 17 ). It seems that lowering pH to even 4.5 can increase the time of column incubation and the temperature of incubation leading to the efficient cleavage of intein 1 ( 18 ). One study performed on the cleavage of a mutated form of insulin from the intein1 reported that pH 4.5 in comparison to pH 8, and the temperature of 25 °C was more efficient in cleavage ratios ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…reported that the best temperature was considered 37 °C among investigated temperatures ranging from 15 to 37 °C for Ssp DnaB mini-intein fused to human GLP-1/7-36 ( 17 ). It seems that lowering pH to even 4.5 can increase the time of column incubation and the temperature of incubation leading to the efficient cleavage of intein 1 ( 18 ). One study performed on the cleavage of a mutated form of insulin from the intein1 reported that pH 4.5 in comparison to pH 8, and the temperature of 25 °C was more efficient in cleavage ratios ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…It seems that lowering pH to even 4.5 can increase the time of column incubation and the temperature of incubation leading to the efficient cleavage of intein 1 ( 18 ). One study performed on the cleavage of a mutated form of insulin from the intein1 reported that pH 4.5 in comparison to pH 8, and the temperature of 25 °C was more efficient in cleavage ratios ( 18 ). The present study used the incubation temperature of 25 °C for 24 h at pH 6.5 according to the IMPACT manual.…”
Section: Discussionmentioning
confidence: 99%